KONSEP PENGETAHUAN DALAM THE IDEA OF A UNIVERSITY DARI JOHN HENRY NEWMAN - Balela, Yoseph Solor (UNIKA Santo Thomas, 2003)
For Newman, knowledge is an exercise of the intellect to develop the habit of viewing the objects as a unity, like an encyclopaedia, or a circle or a concert. Knowledge is not only a result of the â€œpassiveâ€ action of the memory, but the â€œactiveâ€ action of the intellect. Knowledge is an education of the intellect to become a gentleman related to liberal knowledge (knowledge for knowledge) and to be a useful man related to useful knowledge. These aims are natural and secular. As a Christian, Newman needs more. Newman needs a religious knowledge also. Newman refuses to separate thinking about religion from other kinds of thinking. He wants an integral knowledge; Newman wants an â€œintegralâ€ education for an â€œintegralâ€ man. The appropriate place for an integral education is a university. In a world that is moving towards a society based on diversity, fragmentarity, discontinuity, multi-versity, Newman wants a society based on unity in diversity, based on â€œuni-versityâ€.